Antica e nuova sinodalità. Una comparazione (Stato, Chiese e pluralismo confessionale, 2025)
Old and New synodality. A Comparative StudyThe objective of the present essay is to contextualise past and post-Vatican II forms of synodality within their respective historical and ecclesiological frameworks. The initial stage will entail an examination of the premises underlying Pope Francis' synodal vision and the innovations he has introduced through the reform of the Synod of Bishops. Subsequently, an account will be provided of the distinctive forms of the synodal tradition in the Latin Church. Particular attention is paid to the significant experiences of both the first and the second millennium, with a particular focus on the latter, which has been unjustifiably neglected or considered irrelevant. On this basis, it is possible to identify the differences in context, presuppositions, method and purpose between the synodality of the past and the synodality of the present. Finally, the main changes introduced by Pope Francis in the concept of synodality are highlighted in order to provide useful criteria for understanding the possible implications for the Church's constitutional model.SOMMARIO: Premessa metodologica - 1. Genesi della nuova sinodalità - 1.1. La visione sinodale di papa Francesco - 1.2. La riforma del Sinodo dei vescovi - 2. Due genealogie e modelli distinti - 2.1. Il contesto della tradizione sinodale - 2.2. Il contesto della nuova sinodalità - 2.3. Le differenze di natura, di partecipazione, di metodo e di finalità - 2.4. I modelli ecclesiologici retrostanti - 3. Le metamorfosi della sinodalità - 3.1. Dalla sinodalità episcopale alla sinodalità del popolo di Dio - 3.2. Dalla sinodalità come evento alla sinodalità come stile - 3.3. Dalla sinodalità deliberativa alla sinodalità del discernimento - 4. Conclusioni.